Yield And Quality Of Starfruit (Averrhoa Carambola Cv. B10) Under Protected Cultivation - Mahmood, Zabedah (2007)

(untitled)
Starfruit (Averrhoa carambola) is an important export fruit with an annual export value of RM30 million. The fruit is mainly exported to Europe. A critical constraint to the future expansion of the starfruit industry is its high labour requirement especially in wrapping of individual fruits, which takes up about 45% of the labour cost. Besides the labour requirement, from 2004 onward all fresh produce to be exported to Europe must meet the EUREPGAP requirement, which encompasses a good agriculture practice such as minimum usage of agrochemicals to maintain consumer confidence in food quality and safety. Thus cultivation of starfruit under protected structure offers an alternative production technique that can be considered. Three experiments were conducted to study the agronomic performance of starfruit under protected structure. The first study was on the effect of crop load on plant’s physiological performance, yield and fruit quality. The rate of stomatal conductance and transpiration of matured leaf (35 day old) was significantly affected by the crop load treatments. The stomatal conductance of the high and medium crop load were 83-93 % higher (P ≤ 0.05) than the low crop load. At the same time the transpiration rate of the middle and high crop load were 91 % higher than the lowest crop load (P ≤ 0.05). The yield increased significantly (P ≤ 0.05) with increase in crop load from 6.3 t/ha at the lowest to 22 t/ha at the highest crop load. The number of exportable size fruit increased with increase in number of ‘M’ and ‘S’ size fruits at the highest crop load. Increase in crop load did not affect the fruit chemical properties such as soluble solids and ascorbic acid concentration. The fruit firmness was not significantly influenced by the crop load treatments. Thus maintaining crop load of starfruit up to 600 fruit per trees per harvesting season was able to increase exportable yield of starfruit without affecting fruit chemical properties and fruit firmness. The second experiment was on the effect of fruit microenvironment on fruit development, qualities and nutrient concentration. The position of fruit under the tree canopy influenced the fruit microenvironment such as heat units and cumulative irradiance impinging on the fruits. The difference in heat units and cumulative irradiance had significant influence on fruit development, and fruit chemical properties. The fruits that were exposed to higher irradiance (PAR m.m-2) were lower in fruit fresh weight (P ≤ 0.05) compared to fruits protected under the canopy. Thus at harvest these fruits were small and mainly of the ‘S’ size, while fruits protected under the tree canopy were bigger mainly of ‘M’ size. Exposure to higher irradiance (PAR m.m-2) did not influence the soluble solids concentration. Although exposure to higher irradiance could increase the ascorbic acid and carotenoid concentrations, the fruits lacked lustre. Exposure to higher heat unit caused a reduction in fruit calcium, which was the only element that was found to influence firmness of starfruit. Hence a third study was conducted to determine the effect of foliar calcium on fruit quality improvement. Application of calcium onto the fruit during the early fruit development stage resulted in increase in fruit calcium concentration from 228 mg/kg to 287 mg/kg (P ≤ 0.05). The calcium treated fruits had smaller cells with thicker cell walls when examined under the electron microscope. The application of calcium also increased the wing tip thickness (P ≤ 0.05). In conclusion, when cultivated under protected structure yield of starfruit can be increased by increasing the crop load up to 600 fruits per tree without adverse effect on fruit quality. Best quality fruits were those protected under the tree canopy. Application of the foliar calcium on to the fruit further enhanced fruit quality, resulting in fruit with thicker wings and increased in firmness.